2019
DOI: 10.26499/surbet.v14i2.126
|View full text |Cite
|
Sign up to set email alerts
|

Flouting Maxims in Hitam Putih Talk Show

Abstract: Communication between speakers and hearer should fulfil maxims in order to have an effective communication and to avoid misunderstanding. In fact, sometimes people blatantly flout the maxims but people mostly have reasons behind that and whenever a maxim is flouted there must be an implicature to save the utterance from simply appearing to be a faulty contribution to a conversation. The importantance of the research is about finding out the dominant flouting of maxims during the conversation between the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…This topic examined by numerous previous studies, as in the studies by Aisya and Fitrawati (2019), Marlisa, and Hidayat (2020), Manurung (2019), Fitri, andQodriani (2016), andLestari, Wahyudi, andYusuf (2020).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations

Flouting Maxim in "Spencer" Movie

Ni Nyoman Anyarani Puspaningrum,
Ni Made Verayanti Utami
2023
elysian
“…This topic examined by numerous previous studies, as in the studies by Aisya and Fitrawati (2019), Marlisa, and Hidayat (2020), Manurung (2019), Fitri, andQodriani (2016), andLestari, Wahyudi, andYusuf (2020).…”
Section: Introductionmentioning
confidence: 98%
“…The result from study by Manurung (2019) the writer found that in talk show of Hitam Putih there are several reason to disobey the maxim; first quality maxim: to make a joke and to give clearer information. Second quantity maxim: to avoid unpleasant situation, to give clearer information, and to stress something.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation

Flouting Maxim in "Spencer" Movie

Ni Nyoman Anyarani Puspaningrum,
Ni Made Verayanti Utami
2023
elysian
“…Maxim of quantity occurs when the participants give required information, and there is no adding of any more information other than the required one Yule (1996).If the participants give too much information or not required information, it can be stated that the participants have flouted the quantity maxim. The flouting of quantity maxim is shown in an article by Manurung (2019).…”
Section: Introductionmentioning
confidence: 99%
“…Here is the review of the previous research. First, (Manurung, 2019) studied the most dominant type of flouting of maxims in an Indonesian Talk Show, Hitam Putih, and the reasons why the speakers flout the maxim. The result shows that the most dominant maxim flouted is the maxim of quality.…”
Section: Introductionmentioning
confidence: 99%